2020
DOI: 10.1002/jsfa.10488
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic and shelf life of fish sausage: fortification with fish oil through emulsion and gelled emulsion incorporated with green tea extract

Abstract: BACKGROUNDSilver carp (Hypophthalmichthys moltrix) fish sausages incorporated with three forms of refined cod liver oil (as a source of polyunsaturated fatty acids: fish oil, oil‐in‐water emulsion (E), gelled oil‐in‐water emulsion (G)) and lyophilized aqueous extract of green tea (Camellia sinensis; 700 and 900 mg kg−1) were developed. The composition, technological properties (cooking loss, pH, texture, and color), sensory analysis, and microbial and oxidative stability of fish sausages during storage (4 °C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
2
10
0
1
Order By: Relevance
“…The addition of CLO in mince sausages did not influence (p > .05) the pH of the sausages in the present study and is considered within a normal range in products. Similar pH values were reported for control and fish oil containing silver carp sausages on the initial day of storage (Pourashouri et al, 2020). In contrast to the present results, Cáceres et al (2008) reported that an increase in pH was related to the pre-emulsion components such as caseinates used for the incorporation of fish oil in a Spanish bologna-type sausage.…”
Section: Effects Of Clo On the Proximate Composition And Ph Of Mince Sausagessupporting
confidence: 82%
“…The addition of CLO in mince sausages did not influence (p > .05) the pH of the sausages in the present study and is considered within a normal range in products. Similar pH values were reported for control and fish oil containing silver carp sausages on the initial day of storage (Pourashouri et al, 2020). In contrast to the present results, Cáceres et al (2008) reported that an increase in pH was related to the pre-emulsion components such as caseinates used for the incorporation of fish oil in a Spanish bologna-type sausage.…”
Section: Effects Of Clo On the Proximate Composition And Ph Of Mince Sausagessupporting
confidence: 82%
“…The intake of fatty acids can also promote the growth and functioning of the immune system (40,142,222,226). To increase ω-3 fatty acid content, Pourashouri et al (143) introduced fish oil into fish sausage. There are some benefits to the use of fish oil-loaded nanoemulsions (as opposed to bulk oils) to enhance processed ω-3 fatty acid in meat and fish-based food products.…”
Section: Meat and Fish-based Productsmentioning
confidence: 99%
“…Penyimpanan dalam freezer bisa mencapai 2 minggu sampai 1 tahun (Suryatmoko, 2010). Daya simpan nuget meningkat dengan penambahan ekstrak tumbuhan seperti ekstrak teh (Pourashouri, et. al.…”
Section: Pendahuluanunclassified